Temporary Segmental Distraction in a Dog with Degenerative Lumbosacral Stenosis - Willems, Nicole; Kersten, Roel F.M.R.; van Gaalen, Steven M.; Öner, F. Cumhur; Strijkers, Gustav J.; Veraa, Stefanie; Beukers, Martijn; Tryfonidou, Marianna A.; Meij, Björn P. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objectives Degenerative lumbosacral stenosis (DLSS) is characterized by intervertebral disc degeneration and causes lower back pain in dogs. Temporary distraction in rabbit models with induced intervertebral disc degeneration showed signs of intervertebral disc repair. In the present study, we assessed safety and efficacy of temporary segmental distraction in a dog with clinical signs of DLSS.Methods Distraction of the lumbosacral junction by pedicle screw–rod fixation was applied in a 5-year-old Greyhound with DLSS and evaluated by radiography, magnetic resonance imaging, and force plate analysis before and after distraction.Results Safe distraction of the lumbosacral junction was demonstrated, with improvement of clinical signs after removal of the distraction device. Signal intensity of the intervertebral disc showed no changes over time. T2 value was highest directly after removal of the distraction device but decreased by 10% of the preoperative value at 9 months of follow-up. Disc height decreased (8%) immediately after removal of the distraction device, but recovered to the initial value. A decrease in the pelvic/thoracic propulsive force during pedicle screw–rod fixation and distraction was demonstrated, which slowly increased by 4% compared with the initial value.Clinical significance Temporary pedicle screw–rod fixation in combination with distraction in a dog with DLSS was safe, improved clinical signs and retained disc height at 9 months of follow-up.
Keywords: degenerative lumbosacral stenosis; dog; intervertebral disc; lower back pain; distraction